2009
DOI: 10.1007/s11552-009-9232-5
|View full text |Cite
|
Sign up to set email alerts
|

An Osteochondroma Limiting Flexion of the Proximal Interphalangeal Joint in Hereditary Multiple Exostosis: A Case Report

Abstract: We describe a patient in which an osteochondroma, which resulted from hereditary multiple exostoses, limited flexion of the proximal interphalangeal (PIP) joint at birth. The tumor grew over the original distal head of the proximal phalanx, and the early appearance of a second ossification center on the base of the middle phalanx was observed. The mass was removed surgically when the patient was 17 months old. There was an improvement in the range of motion at a follow-up evaluation 3 years later. The tumor sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Legeai-Mallet et al state in their series with 175 patients who had at least two exostoses of the juxta-epiphyseal region of the long bones that HME was detected in some patients at birth, before 5 years in most, and all before the age of 12 years, with the median age of diagnosis at 3 years of age [35]. Khan [60].…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Legeai-Mallet et al state in their series with 175 patients who had at least two exostoses of the juxta-epiphyseal region of the long bones that HME was detected in some patients at birth, before 5 years in most, and all before the age of 12 years, with the median age of diagnosis at 3 years of age [35]. Khan [60].…”
Section: Agementioning
confidence: 99%
“…Solomon et al report that 65% [52] and Leone et al report that 89% [36] of these patients are identified before at 6 years of age. In 2009, Yoshioka et al report a 24-day-old patient with stiffness at the right long finger due to an osteochondroma from HME, who they operated on at 17 months of age [60].…”
Section: Introductionmentioning
confidence: 99%